Legislative Delegation - Iancu, Bogdan. author. aut Link
XII, 292 p.
Keywords: An overarching question of contemporary constitutionalism is whether equilibriums devised prior to the emergence of the modern administrative-industrial state can be preserved or recreated by means of fundamental law. The book approaches this problem indirectly, through the conceptual lens offered by constitutional developments relating to the adoption of normative limitations on the delegation of law-making authority. Three analytical strands (constitutional theory, constitutional history, and contemporary constitutional and administrative law) run through the argument. They merge into a broader account of the conceptual ramifications, the phenomenon, and the constitutional treatment of delegation in a number of paradigmatic legal systems. As it is argued, the development and failure of constitutional rules imposing limits on legislative delegation reveal the conditions for the possibility of classical limited government and, conversely, the erosion of normativity in contemporary constitutionalism.